An Analysis Of Three Curriculum Approaches In Teaching English At Schools - Rizki Hasanah; Siminto Siminto; Zaitun Qamariah (BADAN PENERBIT STIEPARI PRESS, 2023)
This research aims to find out the differences and explain the 3 curriculum approaches. This research uses a descriptive qualitative approach with library research methods. The data collection technique is to collect several references, such as books, articles, and other related sources. Then the data analysis techniques used in this study are content analysis, with stages of data display, data reduction, data verification, and conclusion . In this study using qualitative research. The data analysis method used in this research is descriptive qualitative method. The results showed there is no best approach to curriculum design, and that forward design, central design and backward design may each work well but in different circumstances. Each approach has advocates and practitioners who can cite examples of their successful implementation. They may also work simultaneously in some circumstances.